2021
DOI: 10.1108/jfm-11-2020-0087
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between managerial entrenchment and accounting conservatism

Abstract: Purpose This study aims to assess the relationship between managerial entrenchment and accounting conservatism in Iran. Design/methodology/approach To test hypotheses, all listed companies on the Tehran Stock Exchange during 2013–2018 (six years) that qualified were selected. Given the defined limitations of the study, a total of 120 firms with 720 year-observations was selected. After collecting data and figures, they were analyzed using EViews software. Having presented the inferential model tests, the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The findings showed that when accounting is conservative, it is possible to deduce the amount of risk and predict stock returns using accounting-and market-based indicators. Salehi et al, (2021)all listed companies on the Tehran Stock Exchange during 2013-2018 (six years examined the connection between management entrenchment and accounting conservatism in Iran.…”
Section: Accounting Conservatism Based On Both Acruals and Market Valuementioning
confidence: 99%
“…The findings showed that when accounting is conservative, it is possible to deduce the amount of risk and predict stock returns using accounting-and market-based indicators. Salehi et al, (2021)all listed companies on the Tehran Stock Exchange during 2013-2018 (six years examined the connection between management entrenchment and accounting conservatism in Iran.…”
Section: Accounting Conservatism Based On Both Acruals and Market Valuementioning
confidence: 99%